2018
DOI: 10.1038/s41598-018-28609-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Dynamics after Single- and Three-piece Acrylic Intraocular Lens Implantation: A Swept-source Anterior Segment Optical Coherence Tomography Study

Abstract: Accurate alignment of an intraocular lens (IOL) is indispensable for achieving accurate postoperative refractive outcomes. Thus, we evaluated decentration and tilt of single- and three-piece IOLs, as well as anterior chamber depth (ACD), at 3 hours, 24 hours, 2 weeks, and 4 weeks after cataract surgery, using swept-source anterior segment optical coherence tomography. There was no significant difference in postoperative visual acuity between eyes with single- or three-piece IOLs. Absolute values of IOL decentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…Kemer et al [ 38 ] reported the mean IOL tilt angle of 3.80° ± 4.09° in the horizontal axis and 2.83° ± 4.03° in the vertical axis in 94 eyes with Z-sutured scleral fixated using AS-OCT without pupil dilation. Barca et al [ 39 ] reported mean tilt of 2.08° ± 1.19° in 32 eyes with a sutureless single piece scleral fixated IOL following pupil dilation and Ibrahim et al [ 40 ] reported lens decentration range between 0.21 mm and 0.9 mm and IOL tilt ranged between 1.2° and 2.8° in 6 patients with suture fixated sulcus IOLs using AS-OCT. CASIA2 (Tomey Corp., Nagoya, Japan) is a second-generation Swept source AS-OCT with scan depth of 13 mm [ 5 ]. It is an efficient method to measure IOL tilt and decentration with high repeatability.…”
Section: Measurement Of Iol Tilt and Decentrationmentioning
confidence: 99%
See 3 more Smart Citations
“…Kemer et al [ 38 ] reported the mean IOL tilt angle of 3.80° ± 4.09° in the horizontal axis and 2.83° ± 4.03° in the vertical axis in 94 eyes with Z-sutured scleral fixated using AS-OCT without pupil dilation. Barca et al [ 39 ] reported mean tilt of 2.08° ± 1.19° in 32 eyes with a sutureless single piece scleral fixated IOL following pupil dilation and Ibrahim et al [ 40 ] reported lens decentration range between 0.21 mm and 0.9 mm and IOL tilt ranged between 1.2° and 2.8° in 6 patients with suture fixated sulcus IOLs using AS-OCT. CASIA2 (Tomey Corp., Nagoya, Japan) is a second-generation Swept source AS-OCT with scan depth of 13 mm [ 5 ]. It is an efficient method to measure IOL tilt and decentration with high repeatability.…”
Section: Measurement Of Iol Tilt and Decentrationmentioning
confidence: 99%
“…In fact compared to the pupil centre, corneal vertex is considered to be a better reference to assess tilt and decentration because it is not affected by pupil shape [ 11 ]. Sato et al [ 5 ] assessed tilt and decentration in short-term postoperative period using CASIA2 (Tomey Corp., Nagoya, Japan) and found very high inter-observer and intra-observer reproducibility.…”
Section: Measurement Of Iol Tilt and Decentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…The degree of IOL decentration and tilt was measured using swept-source anterior segment optical coherence tomography (AS-OCT, CASIA2, Tomey Corp., Nagoya, Japan) [12,13]. This instrument performs a three-dimensional analysis with 16 different angles of AS-OCT images, then automatically measures the amount of IOL decentration and tilt relative to the visual axis.…”
Section: Examinationsmentioning
confidence: 99%